Marketing Strategies of Busung Tourism Village for Achieving Sustainable Tourism in Bintan Regency - Panjaitan, Debby Sri Chintya; Darmawan, Rahmat; Ngatemin (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
Sustainable tourism has become a strategic issue in preserving environmental sustainability and local cultural heritage in Bintan’s tourism villages. This study aims to formulate effective marketing strategies for Busung Tourism Village in Bintan Regency using in-depth interviews and the Boston Consulting Group (BCG) Matrix analysis. Data were collected through interviews with representatives of the Bintan Office of Culture and Tourism, the Head of Busung Village, and the Generasi Pesona Indonesia (GenPI) Bintan community. The findings indicate that Busung Tourism Village has major strengths, including cultural diversity and natural attractions that enhance its appeal. However, limited promotional activities and inadequate hospitality services remain significant weaknesses. The study also identifies opportunities from the increasing global interest in sustainable travel, while competition from other destinations poses a major challenge. Based on the analysis, the recommended strategies include strengthening destination branding, optimizing digital promotion, and expanding collaboration with external stakeholders. The study concludes that integrated marketing strategies can improve the competitiveness of Busung Tourism Village while supporting sustainable tourism development and community empowerment.